ILLEGAL MINING AND THE HEALTH OF THE YANOMAMI PEOPLE - Teixeira Cunha, Wéltima (Revista Binacional Brasil-Argentina: Dialogue between the sciences, 2023)
Mercury is a metal that has been extensively studied due to its usage and harmful consequences to humans and the ecosystem. This is mainly attributed to its toxic effects on human health and environmental contamination, as described and proven in literature. The territory of the Yanomami people borders between Brazil and Venezuela, located north of Roraima, south of Venezuela, and northeast of the Brazilian Amazon. The subsistence of these indigenous people relies on the wealth of the Amazon rainforest, coupled with their respectful wisdom passed down through generations and the cultivation of their crops. Therefore, the objective is to disseminate information regarding the harmful effects of mercury on the health of the Yanomami people in the past four years, as well as the underlying causes influencing malnutrition, diseases, and death among these indigenous communities. The bibliographic research was conducted using reliable sources such as books and websites, which document an exclusive reality and potential extermination. The research highlights the detrimental effects caused by invading miners on the health of the Yanomami people and the ecosystem.